Application of a bioclimatic tool for the hygrothermal analysis of a historic building in Lima-Peru. Issue 1 (1st January 2022) - Alvarez, S; Lefebvre, G
Abstract: The main objective of this paper is to know and analyze the bioclimatic strategies that would be present in colonial residential architecture in Lima. The knowledge and use of systems to achieve certain climate conditions in ancient buildings made of sun-dried bricks and thatch, both in open and closed spaces. We consider that through trial-and-error approaches, techniques would have been developed to obtain indoor comfort considering local climate conditions, available materials and other cultural conditions. Temperature, humidity and air speed measurements were taken three times a day during four days in some places of the building. Givoni's building bioclimatic chart is used to analyze the performance of the places measured. On the one hand, different climate conditions were recorded in each patio and would be the result of its physical characteristics. In addition, differences between the performance of social spaces and private rooms were observed due to different ventilation strategies.